2008
DOI: 10.1086/589498
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy Properties of PKS 1830−211

Abstract: We report an analysis of X-ray and -ray observations of PKS 1830À211, based on long-term campaigns carried out by INTEGRAL and COMPTEL. The INTEGRAL data currently available provide a 33 significance detection in the 20-100 keV band, while the COMPTEL 6 yr data provide a 5.2 significance detection in the 1-3 MeVenergy band. In hard X-rays, INTEGRAL and supplementary Swift observations show flux variability on timescales of months. In -rays, the source shows persistent emission over years. The hard X-ray spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…XMM-Newton observations of PKS 1830−211 were modeled by Foschini et al (2006) with a broken power-law model, with the photon index changing from ∼1.0 to ∼1.3 at about 3.5 keV. The joint fit of XMM/INTEGRAL data performed by Zhang et al (2008) confirmed that the broken power law is the best model fit, with column density, photon indices, and energy break parameters very similar to those found in the previously cited works.…”
Section: Swift Xrt Observationssupporting
confidence: 74%
See 2 more Smart Citations
“…XMM-Newton observations of PKS 1830−211 were modeled by Foschini et al (2006) with a broken power-law model, with the photon index changing from ∼1.0 to ∼1.3 at about 3.5 keV. The joint fit of XMM/INTEGRAL data performed by Zhang et al (2008) confirmed that the broken power law is the best model fit, with column density, photon indices, and energy break parameters very similar to those found in the previously cited works.…”
Section: Swift Xrt Observationssupporting
confidence: 74%
“…As a first step we fit the average spectrum with the same model used for the single observations, obtaining an acceptable fit. Leaving the value of the column density of the 2003, COMPTEL (bowtie), and EGRET are taken from the literature (de Rosa et al 2005;Foschini et al 2006;Zhang et al 2008) and are plotted as light-gray open circles with a light-gray dashed-line model. All data are corrected for lensing for a factor of 10 magnification (although note that the magnification may not be the same for all frequencies; see Section 6.1).…”
Section: Swift Xrt Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKS 1830–211 is a gravitationally lensed galaxy and the excess absorption can be attributed to the intervening galaxy at z = 0.89. The best fit of the observed spectrum requires both an absorber and a broken power law (model D), confirming the results reported by Zhang et al (2008) with three XMM–Newton observations (Obs. IDs 0204580201, 0204580301 and 0204580401) 6 and the INTEGRAL average data (up to 2006 April 29).…”
Section: Broad‐band Spectral Analysissupporting
confidence: 86%
“…The most important additional source is the "nearby" quasar PKS 1830-210 at l/b=∼12.2 • /-5.7 • , which is also a known COMPTEL source (e.g. Zhang et al, 2008). The inclusion of two further MeV source, one at the Galactic Center, the other one being the COMPTEL detected blazar PKS 1622-297 (Zhang et al, 2002) showed no influence on the derived source fluxes of GRO J1823-12.…”
Section: Instrument and Data Analysismentioning
confidence: 91%